Unrecognized Primary Hypoparathyroidism with Severe Hypocalcemia in the Presence of COVID-19 Infection - Grigoravičius, Domas; Šiaulienė, Laura; Visockienė, Žydrūnė (Acta medica Lituanica, 2022)
Primary hypoparathyroidism (PHPT) is a rare disease most commonly caused by surgical parathyroid glands destruction or genetic disorders. PHPT manifestation varies from subclinical to acute or even lethal symptoms. In atypical presentation the signs of hypocalcemia could be missed, and asymptotic chronic hypocalcemia could manifest only in the presence of exacerbated comorbidities, infections, hypomagnesemia or certain medications. We present a case of PHPT with severe hypocalcemia manifesting as seizures and delirium in a presence of COVID-19 infection.
Keywords: primary hypoparathyroidism; hypocalcemia; COVID-19